Sie sind auf Seite 1von 3

Wiederholung einiger Ableitungsregeln:

a) y = 3x3
y
nx n1 )
x

(y = xn;

Lsung: x 3 3x

31

9x 2

b) y = 2x3 4x2
y

(Produktregel: y = f(x) g(x); x f (x) g ( x) f ( x) g (x)

y
2
2
3
4
4
4

6
x

4
x

2
x

8
x

24
x

16
x

40
x
Lsung: x

c) y =

4x 4
2x 2

(Quotientenregel: y =

Lsung:

f ( x)
;
g ( x)

y f ( x) g ( x) f ( x) g ( x)

)
x
( g ( x)) 2

y 16 x 3 2 x 2 4 x 4 4 x 16 x 5

4x
x
4x 4
4x 4

d) y = (3x2 + 2)4
y
uere
x

(Kettenregel: y = f(g(x));

Ableitung innere

Ableitung)
y

Lsung: x 4(3x 2 2) 3 6 x

e) y 2 x x x (2 x x x)
3

y 1
6x 2 2x 1
(2 x 3 x 2 x) 3 (6 x 2 2 x 1)
x 3
3 3 (2 x 3 x 2 x) 2
2

Lsung:

1
3

Potenzen
Allgemein

Zahlenbeispiel

a0 1

30 1

a 1

1
a

31

1
3

a n

1
an

34

1
34

32 3

a2 a
a

1
2

1
2

1
3

a m m an

n
m

1
m

an

3 5 5 34
3

4
5

1
5

34

a n a m a nm

3 4 35 3 4 5

a n a n 2a n

34 34 2 34

n m

a nm

4 5

345